Novel method for incorporating hydrophobic silica nanoparticles on polyetherimide hollow fiber membranes for CO2 absorption in gas-liquid membrane contactor - Zhang, Yuan (2013)
In a gas-liquid membrane contactor, a larger pore size can result in a lower membrane mass transfer resistance. However, the membrane pore size is usually limited by the concern of pore wetting, e.g. a large pore size means a higher wetting tendency. As a breakthrough, this paper reported a porous polyetherimide (PEI) hollow fiber membrane with high surface porosity and large pore size to minimize the membrane mass transfer resistance by using a triple-orifice spinneret in the hollow fiber spinning process, and followed by a novel approach of fluorinated silica (fSiO2) nanoparticles (NPs) incorporation to make the membrane surface highly hydrophobic and chemical resistant to prevent the membrane from wetting caused by the large pore size on the membrane surface. The newly developed composite hollow fiber membranes showed the advancing contact angle value of 123.3°, receding contact angle value of 107.2°, and contact angle hysteresis of only 15.9°, indicating the high water resistant property. The composite membrane also exhibited a higher rigidity property compared with original PEI substrate. The CO2 absorption flux of the composite membranes was investigated in both physical and chemical absorptions in a gas-liquid membrane contactor system. The membrane contactor showed a stable performance throughout the 60-day long-term operation using a 2 M sodium taurinate aqueous solution as the liquid absorbent.